Stable isotopes reveal dietary divergence between dispersal phenotypes in Tetrix subulata pygmy grasshoppers (Orthoptera: Tetrigidae) - Einat KARPESTAM; Anders FORSMAN (European Journal of Entomology, 2013)
In some species of insects, individuals with fully developed wings and capable of flying coexist with flightless individuals that lack functional wings. Their diets may differ if long-winged individuals are more mobile and therefore likely to be better at finding and utilizing high quality food resources, or if they have different food preferences or physiological requirements. Despite its potential importance, differences in the diet of dispersal phenotypes have not been unequivocally demonstrated under natural conditions. To test for dietary divergence, we compared natural abundances of carbon and nitrogen stable isotope ratios (d13C and d15N) in long- and short-winged free ranging Tetrix subulata pygmy grasshoppers collected as adults from two natural populations. Overall, this comparison of stable isotopes indicated long-term differences in the diet of the two wing morphs in both populations, but not between males and females of the same morph. We conclude that it is likely that the dietary niches of the long winged and flightless individuals differ under natural conditions. This may reduce intra-specific competition, offset the expected trade-off between flight capacity and reproduction and promote ecological speciation.